PENAMBAHAN L – ARGININ DALAM PENGENCER TRIS KUNING TELUR SETELAH EKUILIBRASI 2 JAM TERHADAP MOTILITAS DAN MEMBRAN PLASMA UTUH SPERMATOZOA DOMBA SAPUDI - Suryaningsih, Hastini; Sabdoningrum, Emy Koestanty; Susilowati, Suherni; Sardjito, Trilas; wurlina, wurlina; Damayanti, Tita (Universitas Airlangga, 2018)
This research was aimed to determine the addition of L-arginine on motility and sperm plasma membrane of Sapudi sheep after two hour equilibration time in egg yolk tris diluent. This research used fresh samples of sheep Sapudi semen collected by artificial vagina, then were devided into 4 treatments and 6 replications. Analysis of the data using Analysis of Variance (ANOVA) then proceed to the Duncan Test to determine significant differences between treatments. The first treatment P0 was no L – Arginine added as control. P1 was treated with 0,004 M L – Arginine. P2 was treated with 0,005 M L – Arginine, P3 was treated with 0,006 M L – Arginine. Result of two hour equilibration time for the sperm motility showed: (P0) 46,67a 5,16, (P1) 49,16ab 5,84, (P2) 55,00bc 7,74, (P3) 58,33c 6,83. Result of two hour equilibration time for the sperm plasm membrane were: (P0) 39,33a 4,92, (P1) 43,33ab 4,22, (P2) 46,50 bc 3,44, (P3) 50,83 c 3,48. The addition of L-arginine with a concentration as much as 0.006 M, shows the highest result in sperm motility and sperm plasm membrane intact of Sapudi semen.